Antibacterial Activity of Germicide-P® : A Persulfate Based Detergent/Disinfectant on Some Hospital Isolates: Antibacterial activity of germicide-P - Lotfipour, Farzaneh; Milani, Morteza; Nahaei, Mohammad Reza; Javaherzadeh, Vahid; Omrani, Amin; Attar, Navid (Iranian Journal of Pharmaceutical Sciences, 2006)
A novel chemical detergent/disinfectant formulated based on persulfate salts, germicide P® , is available for disinfection of surfaces and medical devices at the room temperature. Because of the resistance of hospital-resident microorganisms, the antimicrobial activity of this compound is evaluated in the present study. The tests conducted with this disinfectant included bactericidal tests against 25 clinical isolates of gram negative bacteria of Escherichia coli, Pseudomonas aeruginosa as well as 25 clinical isolates of gram positive bacteria of Staphylococcus aureus with and without 5% bovine serum albumin (BSA) as dirty condition. All of the experiments also performed using standard strains and serial dilution method applied to find minimum bactericidal concentration (MBC) of germicide P® against the selected bacteria at different exposure times. Also, to determine the ability of germicide P® for disinfection of surfaces, standard surface tests were conducted using all of the clinical isolates as well as standard strains. According to the in vitro results of the tests, germicide P® found to be a promising product with the MBC of 1/10 after 5 min. against all of the tested bacteria at the room temperature, however, the results of the surface tests indicated that a significant reduction in the efficacy of germicide P® was observed and the MBC dropped to 1/5. In conclusion, surface antisepsis without intervention of organic materials in the concentration range of 1/5 was achieved with this new disinfectant.